Síndrome de burnout y rendimiento laboral docentes de la Unidad de Educación a Distancia y en Línea, de la UNL, periodo actual - Ramírez Pineda, Gabriela Stefani (2025)
The research analyzed the impact of Burnout syndrome on the work performance of teachers of the Distance and Online Education Unit of the National University of Loja. This phenomenon, which is characterized by emotional exhaustion, depersonalization and low personal fulfillment, negatively affects the quality of life and professional performance of academics. The study also sought to identify how work overload and lack of resources influence Burnout, analyze its impact on teacher motivation and develop an intervention plan that includes emotional management workshops and group counseling. A mixed approach was used, combining qualitative and quantitative techniques. For data collection, the Maslach Burnout Inventory (MBI) questionnaire and a work performance evaluation instrument were applied, which allowed obtaining information from 56 teachers selected by intentional sampling. The results showed that 75% of the teachers presented low levels of emotional exhaustion, while 10.7% presented high levels. In addition, 89% reported low levels of depersonalization, and a considerable percentage indicated low personal fulfillment, which affected their motivation and performance. In addition, the findings that were identified gave rise to the urgency of establishing policies to reduce work stress through wellness programs, such as training in emotional management and group support sessions. The findings showed that Burnout has a direct impact on the quality of academic work, which highlights the importance of preventive strategies and psychosocial support. Finally, an intervention plan was proposed that included activities such as stress management workshops, work recognition programs and individual counseling for teachers